PENINGKATAN PEMAHAMAN SIKLUS HIDUP PRODUK DAN PEMASARAN DIGITAL PADA KELOMPOK TANI IKAN DI DESA DONOHARJO - Antonius Satria Hadi; Ardhi Khairi; Cahya Purnama Asri; Bhenu Artha; Utami Tunjung Sari (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2021)
This community service activity to give counseling to fish farmer groups in Dukuh Brengosan, Donoharjo Village, Ngaglik, Sleman, Yogyakarta Special Region which aims to provide additional understanding and knowledge to the fish farmer group "Mujur Fish Farm" about the product life cycle and digital marketing so that existing products can be widely marketed by utilizing e-marketplace. The community service activity aims to increase understanding and additional knowledge to the “Mujur Fish Farm” fish farmer group in Donoharjo Village about the product life cycle and digital marketing which is carried out using lecturing, demonstrating, and question answer methods. The benefits that participants can get from this community service activity include increasing knowledge, understanding, and experience of the "Mujur Fish Farm" fish farmer group in Donoharjo Village about the product life cycle and digital marketing.